Genetic Variations in rplB Gene Associated with Multidrug Resistance Acinetobacter baumannii Isolated from Different Clinical Sources - Hamzah, Alaa Salim (Al-Nahrain Journal of Science, 2018)
In this study, two hundred specimens were collected from patients suffering from urinary tract infection, wound infection, otitis infection and respiratory tract infection (fifty specimens from each infection). After laboratory diagnosis by biochemical tests and confirmation by advance tests (VITEK- 2 Compact system), only twenty isolates were diagnosed as Acinetobacter baumannii (10%). Then sensitivity test was carried out of all these isolates by using twelve antibiotics, all isolates exhibited various levels of resistance to different antibiotics. Then DNA extraction of all twenty isolates followed by amplification of rplB gene aggainst using PCR with specific primers. DNA sequencing of all isolates was done, then alignmented sequences in NCBI and drew phylogenetic tree by using Geneious 9 software among locally isolates alone and then between them and high identity globally identified registred isolates in Gene Bank. Distribution of locally isolates in phylogenetic tree showed three different groups. The phylogenetic tree showed there were eight locally isolates differed from the standard isolates. From these locally isolates, one isolate (AE_12) was documented in NCBI under accession number (LOCUS KY818058) of nucleotides sequence and protein ID "ARV90996.1".